PENGARUH KEAHLIAN PENGGUNA TERHADAP KINERJA SISTEM INFORMASI DENGAN VARIABEL INTERVENING PARTISIPASI, KECEMASAN, KEPUASAN, DERAJAT PENERIMAAN, DAN KETIDAKPASTIAN KERJA - Kustono, Alwan Sri (Optimal: Jurnal Ekonomi dan Kewirausahaan, 2011)
Development of information system (IS) is crucial action in the organization. Different contextual variables have been found to affect various aspects of the information system project The purposes of this research are to study the impact of implementation of computer based system information in banks. User participation, user skills, computer anxiety, user satisfaction to use IS, user acceptance, and job uncertainty classified as variables exogenous. Endogenous variable is performance of  information systems. There were fourteen hypothesis would be examined. Data for the study were collected from 100 banks in East Java through questionnaire responses. Results indicate user skills affect to user participation of IS implementation and level of computer anxiety. Also, users participation affect to motivation, user acceptance, and job satisfaction. The performance of IS was influenced job satisfaction, and user acceptance